Chasing Digital - Stevens, Anthony; Strauss, Louis (Ascent Audio, 2019)
Learn how to succeed in the digital economy The paradigms of big business have changed. Business models that were once lucrative now seem to barely move the needle. Incumbents of the old guard find themselves superseded by new, digitally-charged, data-fueled organisations that leverage platform-based business models. How can pre-digital businesses survive? They're loaded with resources, brand power and deeply embedded networks, they just need a new playbook. Chasing Digital is that playbook. Outlining a clear and detailed framework, this book is designed to help leaders re-design their organisation from the bottom up by leveraging their strengths to create a new competitive advantage in the digital economy. From laying the foundations of transformation: developing a considered strategy, growing a conducive culture and building a receptive organisational design; to building core digital capabilities: taking advantage of data, harnessing artificial intelligence and embracing appropriate platforms; to adapting the accelerators of change: navigating board expectations, mitigating potential roadblocks and making the right investments, this playbook will give you the tools and mindsets needed to not only survive but to thrive and leave a legacy for future leaders.
Online resource; Title from title page (viewed January 30, 2019)
Keywords: Business; Affaires; Audiobooks